Penyusunan Unit Pembelajaran Inquiry Based Learning Berorientasi Kemampuan Abad 21 - Feriansyah Sesunan; Abdurrahman; Novinta Nurulsari; Hervin Maulina (Universitas Lancang Kuning, 2021)
The context of learning in the 21st century directs teachers to think whether they will continue to play the role of